2019
DOI: 10.1186/s12885-019-6212-1
|View full text |Cite
|
Sign up to set email alerts
|

Clear cell sarcoma of the kidney in a 62-year-old patient presenting with generalized pruritus

Abstract: BackgroundClear cell sarcoma of the kidney (CCSK) is the second most common renal tumor in children following Wilms’ tumor. CCSK is extremely rare in adults, with only 25 adult cases reported in the medical literature.Case presentationWe reported a 62-year-old man with a right renal mass presenting only with generalized pruritus who underwent radical right nephrectomy. With immunostaining, tumor cells were positive for expressed vimentin, neural cell adhesion molecule (NCAM, CD56), and Ki-67 and focally positi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 54 publications
0
1
0
Order By: Relevance
“…Other symptoms included hypertension (one case), metastatic temporal area mass (one case), and weight loss (one case). Zhang et al ( 5 ) reported a case presenting with generalized pruritus. They believed that the pruritus in their patient was caused by paraneoplastic itch.…”
Section: Discussionmentioning
confidence: 99%
“…Other symptoms included hypertension (one case), metastatic temporal area mass (one case), and weight loss (one case). Zhang et al ( 5 ) reported a case presenting with generalized pruritus. They believed that the pruritus in their patient was caused by paraneoplastic itch.…”
Section: Discussionmentioning
confidence: 99%